EVALUASI KESESUAIAN LAHAN TANAMAN CABAI PIPER RETROFRACTERUM di KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Ahmad Fikrizal (DEPARTEMEN GEOGRAFI FIS UNP, 2018)
This research was conducted on Kamang Magek Subdistrict, Regency of Agam, in December 2016 aimed to get data and information about (1) Characteristic of land related to the requirement of growth of chilli plant (2) Land suitability of chilli area area in research area. The research includes descriptive research type, the sample is taken from the map of the unit of land form obtained from the overlay of landform map with slope map, soil type map, geological map, land use map. Data analysis techniques used to determine land characteristics and land suitability is the method of matching or matching each land characteristic. The results showed (1) The level of land suitability consisted of the corresponding level (S2) of three units of land. (2) Land suitability characteristics in the study area have varying slopes from flat (0-8%), ramps (8-14%), steep slopes (8-14%), steep slopes (25-40%), very steep (> 40%)., Clay. Soil pH ranges from 5.05 to 6.75. Permeability between 2.91-axis (infinity). Rainfall 1898,5 mm / yr. The dry season is 8 and the temperature is 210 C. It consists of 3707.51 ha of forest, mixed plantation with an area of ​​511.67 ha, the moor has an area of ​​624.48 ha, the bush has an area of ​​1877.44 ha, the rice field has an area of ​​1877 , 44 Ha and the settlement has an area of ​​369.54 Ha.